The Interactome of the Glucocorticoid Receptor and Its Influence on the Actions of Glucocorticoids in Combatting Inflammatory and Infectious Diseases - Petta, Ioanna (Microbiol Mol Biol Rev, 2016)
Glucocorticoids (GCs) have been widely used for decades as a first-line treatment for inflammatory and autoimmune diseases. However, their use is often hampered by the onset of adverse effects or resistance. GCs mediate their effects via binding to glucocorticoid receptor (GR), a transcription factor belonging to the family of nuclear receptors. An important aspect of GR's actions, including its anti-inflammatory capacity, involves its interactions with various proteins, such as transcription factors, cofactors, and modifying enzymes, which codetermine receptor functionality. In this review, we provide a state-of-the-art overview of the protein-protein interactions (PPIs) of GR that positively or negatively affect its anti-inflammatory properties, along with mechanistic insights, if known. Emphasis is placed on the interactions that affect its anti-inflammatory effects in the presence of inflammatory and microbial diseases.